Review of the genus Malacoctenus (Actinopterygii: Labrisomidae) from the Southwestern Atlantic, with description of two new species - Carvalho-Filho, Alfredo; Sazima, Ivan; Lima, Sergio Maia Queiroz; Almeida, Daniel; Mendes, Liana; Dias, Ricardo Marques; Britto, Marcelo R.; Gasparini, João Luiz (Zootaxa, 2020)
The labrisomid genus Malacoctenus from Southwestern Atlantic is reviewed. Two new species of scaly blennies formerly reported by several authors as Malacoctenus triangulatus are described. One is found at the oceanic islands Fernando de Noronha Archipelago and Atol das Rocas, and the other is distributed along the Brazilian coastline. The two new species differ from other species of the genus and from each other by different combinations of the number of lateral-line scales, number and size of head cirri, and color pattern. Molecular data also support species’ distinctiveness between M. triangulatus and the species described herein. Two additional recognized Brazilian species, M. delalandii and M. brunoi are described and illustrated and an identification key to all recognized Atlantic species is provided.